1995
DOI: 10.1103/physrevlett.74.399
|View full text |Cite
|
Sign up to set email alerts
|

Electron Holography Surmounts Resolution Limit of Electron Microscopy

Abstract: In high resolution electron off-axis holography, the complete information about amplitude and phase of the complex electron image wave is captured in a single hologram, fed to a computer, numerically reconstructed, and analyzed using methods of wave optical image processing. Specifically, the blurring effect due to the aberration of the objective lens of the electron microscope is corrected under reconstruction.The presented first results, achieved with a Philips CM30FEG electron microscope specially developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(57 citation statements)
references
References 13 publications
1
56
0
Order By: Relevance
“…Beyond this limit, the information is corrupted and contrast reversals occur. Various techniques have been suggested in order to solve for the phase of the image-plane wave function, such as off-axis holography (Lichte, 1991;Orchowski, Rau & Lichte, 1995) and focal-series reconstruction (Van Dyck, Op de Beeck & Coene, 1993). Knowledge of the image phase informa-tion allows the lens aberrations to be deconvolved, thus extending the resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond this limit, the information is corrupted and contrast reversals occur. Various techniques have been suggested in order to solve for the phase of the image-plane wave function, such as off-axis holography (Lichte, 1991;Orchowski, Rau & Lichte, 1995) and focal-series reconstruction (Van Dyck, Op de Beeck & Coene, 1993). Knowledge of the image phase informa-tion allows the lens aberrations to be deconvolved, thus extending the resolution.…”
Section: Introductionmentioning
confidence: 99%
“…those that operate in the mid-voltage range around 300 kV and use coherently scattered electrons, an information limit of 0.10 nm was reported already in 1993 8 . Electron holography exploited this information limit down to 0.104 nm 9 . Alternatively, it was reported that a direct reconstruction of the phase and the amplitude of the scattered electron wave from a focal series of HRTEM images is suitable to extend the interpretable resolution of a field emission microscope down to its information limit 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the resolution of these techniques is limited to the pointresolution of the microscope, which typically ranges from 1.7 Å to 2.5Å for midvoltage TEMs. More recently, significant experimental and computational advancements have been made in HRTEM-based techniques designed to retrieve the electron wave function at the exit surface of the specimen [15][16][17]. The use of exit-plane wave function (EPWF) images offers important advantages over existing methods.…”
Section: Quantifying Stoichiometry Of Iii-v Semiconductor Interfacesmentioning
confidence: 99%